International entrepreneurship and geographic location: an empirical examination of new venture internationalization - Fernhaber, Stephanie A; Gilbert, Brett Anitra; McDougall, Patricia P (Journal of International Business Studies, 2008)
In this paper, we argue that geographic location may be one reason why some ventures are able to acquire the resources needed to internationalize while others cannot. We use ecological arguments to predict an inverted U-shaped relationship between the concentration of industry clustering within a geographic location and the venture's internationalization. We also explore whether venture characteristics influence the nature of this relationship. Our hypotheses are regressed on international intensity and scope, and analyzed through a sample of 156 publicly held new ventures. Results confirm that location influences new venture internationalization, and firm characteristics impact the nature of the relationship.